The transcription factor prospero homeobox protein 1 is a direct target of SoxC proteins during developmental vertebrate neurogenesis. Issue 3 (30th July 2018) - Jacob, Anne; Wüst, Hannah M.; Thalhammer, Johannes M.; Fröb, Franziska; Küspert, Melanie; Reiprich, Simone; Balta, Elli‐Anna; Lie, D. Chichung; Wegner, Michael; Sock, Elisabeth
Abstract: The high‐mobility‐group domain containing SoxC transcription factors Sox4 and Sox11 are expressed and required in the vertebrate central nervous system in neuronal precursors and neuroblasts. To identify genes that are widely regulated by SoxC proteins during vertebrate neurogenesis we generated expression profiles from developing mouse brain and chicken neural tube with reduced SoxC expression and found the transcription factor prospero homeobox protein 1 (Prox1) strongly down‐regulated under both conditions. This led us to hypothesize that Prox1 expression depends on SoxC proteins in the developing central nervous system of mouse and chicken. By combining luciferase reporter assays and over‐expression in the chicken neural tube with in vivo and in vitro binding studies, we identify the Prox1 gene promoter and two upstream enhancers at −44 kb and −40 kb relative to the transcription start as regulatory regions that are bound and activated by SoxC proteins. This argues that Prox1 is a direct target gene of SoxC proteins during neurogenesis. Electroporations in the chicken neural tube furthermore show that Prox1 activates a subset of SoxC target genes, whereas it has no effects on others. We propose that the transcriptional control of Prox1 by SoxC proteins may ensure coupling of two types of transcription factors that are both required during early neurogenesis, but have at least in part distinct functions. Open Science: This manuscript was awarded with the Open Materials Badge. For more information see:https://cos.io/our-services/open-science-badges/ Abstract : To investigate transcriptional regulation of vertebrate CNS neurogenesis the functional relationship between SoxC and Prox1 transcription factors was determined. SoxC proteins induce Prox1 as a direct target by acting on the promoter (PR) and two distal upstream enhancers (ECR44, ECR40). SoxC proteins directly bind to sites in these elements (dark red ellipses). The resulting coupled expression allows Prox1 and SoxC proteins to regulate neuronal differentiation in a complex relationship. Open Science: This manuscript was awarded with the Open Materials Badge. For more information see:https://cos.io/our-services/open-science-badges/